2000
DOI: 10.1111/j.1469-8749.2000.tb00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired force coordination during object release in children with hemiplegic cerebral palsy

Abstract: Recent studies on hand motor control in children with cerebral palsy (CP) have focused on the coordination of fingertip forces during the grasping and lifting of objects. However, little is known about the ability to replace and release an object from grasp, a function that is just as important for fine dexterity. The present study examines the coordination of fingertip forces during the replacement and release of an object (either 200 g or 400 g) from grasp in 14 children (aged between 7 and 13 years) with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
1
15
0
3
Order By: Relevance
“…Studies comparing grip force between patients with CP and control subjects have reported conflicting results. One study reported decreased maximal grip force in patients with CP (11), while others reported no differences in static grip force between patients with CP and controls (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies comparing grip force between patients with CP and control subjects have reported conflicting results. One study reported decreased maximal grip force in patients with CP (11), while others reported no differences in static grip force between patients with CP and controls (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…For example, muscle coordination and muscle endurance may not be reflected in a maximal voluntary contraction, while they may be similarly important in the performance of skilled manual tasks in daily activities. It is known that patients with CP have deficits in motor control, mainly due to involuntary co-activation of the antagonistic muscles (13). Several studies (12,13) reported an impaired force coordination of fingertip forces, resulting in a prolonged and uncoordinated release of a grasped object.…”
Section: Introductionmentioning
confidence: 99%
“…Na atividade de escrita, apresentou dificuldade para estabilizar o caderno com a mão acometida enquanto escrevia com a mão não acometida. A realização de atividades motoras bimanuais é complexa e difícil para crianças com hemiparesia, principalmente quando tais atividades envolvem movimentos com componentes assimétricos, como recortar um papel com a tesoura e a escrita manual (ELIASSON; GORDON, 2000;HUNG;CHARLES;GORDON, 2004).…”
Section: Resultsunclassified
“…Crianças hemiplégicas evoluem com piora da função manual 29 e sua principal dificuldade será realizar tarefas que requerem manipulação bilateral 30,31 . As maiores modificações na função da preensão palmar ocorrem durante os primeiros anos de vida 29 .…”
Section: Funcionalidadeunclassified